Analysis of the Acceleration of Implementation Time Using the Crashing Method in the Construction of the Purworejo Bridge, Mojokerto Regency - Farchan, Muchamad; Witjaksana, Budi; Sajiyo, Sajiyo (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Bridge infrastructure plays an important role in supporting connectivity and regional economic growth. However, in their implementation, bridge construction projects often face delays due to technical factors such as weather, soil conditions, as well as managerial and coordination constraints. One of them occurred in the Purworejo Bridge construction project in Mojokerto Regency which experienced a delay in progress of -14.88% in the 12th week of implementation. This delay requires accelerated efforts so that the project is not included in the critical contract category. This study seeks to examine the approach of accelerating implementation time through the Crashing method through increasing working hours (overtime) and calculating costs efficiently to mitigate delays. The methodology used includes the formulation of a network using Microsoft Project, the identification of critical paths through the Critical Path Method (CPM), and the calculation of acceleration costs based on Cost Slopes. The results of the analysis show that the acceleration of work can be achieved both technically and economically. This method allows the project to reduce delays, thus removing them from the classification of vital contracts. The study significantly improved the decision-making process for the timely and cost-effective implementation of development projects.